Experimental Design for Variable Selection in data bases - Constanze Pumplün; Claus Weihs; Andrea Preusser (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
This paper analyses the influence of 13 stylized facts of the German economy on the West German business cycles from 1955 to 1994. The method used in this investigation is Statistical Experimental Design with orthogonal factors. We are looking for all existing Plackett-Burman designs realizable by coded observations of these data. The plans are then analysed by regression with forward selection and various classification methods to extract the relevant variables for separating upswing and downswing of the cycles. The results are compared with already existing studies on this topic.
Keywords: 519; Mustererkennung; Experiment; Konjunktur; Zeitreihenanalyse; Theorie; Deutschland; Klassifikationsanalyse